PENERAPAN JOB SAFETY ANALYSIS (JSA) DALAM MENGANALISA KESELAMATAN DAN KESEHATAN KERJA (K3) PADA PROYEK PEMBANGUNAN - Eko Muliawan Satrio; Kartono Wibowo (Jurnal Teknik Sipil dan Arsitektur, 2023)
In a development project there is Occupational Safety and Health (K3) both in planning, implementing and maintaining work. One of the efforts to reduce the risk and danger of work accidents is by applying safety management techniques, namely using Job Safety Analysis (JSA) to support safe and efficient work procedures. The purpose of this research is to analysis the implementation of Occupational Safety and Health (K3) implementation activities with the Job Safety Analysis (JSA) method. Collecting data in this study through the distribution of questionnaires, direct observations and interviews with contractors as service providers, construction management consultants, sub.contractors and foremen in the construction project of the Integrated Science Olympiad Laboratory of MAN 2 Kudus. Data analysis techniques using qualitative metods generally use tabulation of research characteristic through descriptive scales such as high, medium and low. The results of this research explain that the validity test of alla variables in proven valid, while for the reliability test all variables are proven to be reliable and the value of the Relative Interest Index (IKR) data obtained with the â€œimportantâ€ factor. So it can be concluded that the efforts to control Occupational Health and Safety (K3) on the project can be applied and affect the project performance